IMPLEMENTASI KONSEP GREEN CAMPUS PADA PERGURUAN TINGGI UNIVERSITAS RIAU - Mahendra Mahendra; Zulfan Saam; Syafruddin Nasution (Program Pascasarjana Universitas Riau, 2017)
This research held on May until November 2016 in Riau University Jl. Bina Widya Km. 12,5 Simpang Baru Panam, Pekanbaru. The aim of this research was to discover and evaluate implementation of green campus concept on PSLH Riau University policy, provision of enviromentally friendly facilities, and waste management in Riau University area. The kind of this research is quantitative research with survey method. Primary data was obtained from observation result of PSLH Riau University, ESU Riau University, interview and field observation document, while secondary data resource was obtained from literature study which is related with green campus concept. The result showed that PSLH Riau University policy got score 86,7 in implementation criteria was very good, provision of enviromentally friendly facilities in Riau University got score 82,5 in implementation criteria was very good, and waste management in Riau University area got score 27,5 in implementation criteria was not good enough.